Comparative in vitro effectiveness of ceftolozane/tazobactam against pediatric gram-negative drug-resistant isolates. (7th September 2021) - Kanwar, Neena; Banerjee, Dithi; Harrison, Christopher J.; Newland, Jason G.; Qin, Xuan; Zerr, Danielle M.; Zaoutis, Theoklis; Selvarangan, Rangaraj
Abstract : Ceftolozane/tazobactam (C/T), a cephalosporin/beta-lactamase inhibitor combination, was evaluated in vitro vs. 10 comparators against 299 pediatric extended-spectrum-cephalosporin-resistant or carbapenem-resistant (ESC-R/CR) Gram-negative Enterobacteriaceae from three freestanding pediatric centers. Isolates were from urine or other sterile sites of children and adolescents through 21 years of age. Susceptibilities were assayed by microbroth dilution via custom Sensititre plates (Thermo Fisher Scientific). Susceptibility was determined using the Sensititre Vizion® system (Thermo Fisher Scientific). Susceptibility breakpoint criteria were those of the Clinical and Laboratory Standards Institute (CLSI) for 2017, except for colistin (EUCAST 2019). Overall, 87.5% isolates were C/T susceptible (MIC ≤2 μg/ml; MIC50/90, 0.25/4 μg/ml). Susceptibility to C/T was detected more frequently as compared to all other antimicrobials tested except for colistin (95.4%) and meropenem (97.4%). Percent susceptibility to C/T was high for E. coli (91%) and Klebsiella spp . (73.3%). C/T demonstrated good in-vitro activity and high potency against most beta-lactam resistant pediatric Enterobacteriaceae from three geographically diverse U.S. regions.